1995
DOI: 10.1002/roi.2970030107
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic pulse generated in a patient during treatment by pulsed proton radiation beam

Abstract: SUMMARY Acoustic pulses were detected fiom a patient treated by a pulsed proton radiation beam. The dose rate of the proton beam was 0.3 cGy/pulse. The signals from 100 to 700 pulses were accumulated to improve the signal to noise ratio. After accumulation, the random noise level was negligibly small compared to the signal. These results suggest the feasibility of non-invasive monitoring of proton dose distributions in patients by sensing acoustic pulses generated during irradiation by a pulsed proton radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 12 publications
2
78
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Based on the difference between their characteristic proton spills, the protoacoustic pressure amplitude generated by single-bunch synchrotron spills (<1 µs) is expected to be higher than those generated by either clinical cyclotrons, which typically deliver proton spills with ∼50 µs rise and fall times, or clinical synchrotrons, which typically deliver with ∼200 µs rise and fall times. 22 Given the short (<1 µs) spill times and high (up to 100 mA instantaneous 11 ) proton current capabilities, previous observations of the protoacoustic signal have employed linear accelerator, 6 synchrotron, [7][8][9][10][11][12][13][14][15][16][17] and tandem-accelerator 18 proton sources. Protoacoustic signals have also been observed using cyclotron-derived proton beams, 6,19 but these have used custom, modifiable beam lines originally built for research before they were applied to clinical therapy use, and the spill rise times were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Based on the difference between their characteristic proton spills, the protoacoustic pressure amplitude generated by single-bunch synchrotron spills (<1 µs) is expected to be higher than those generated by either clinical cyclotrons, which typically deliver proton spills with ∼50 µs rise and fall times, or clinical synchrotrons, which typically deliver with ∼200 µs rise and fall times. 22 Given the short (<1 µs) spill times and high (up to 100 mA instantaneous 11 ) proton current capabilities, previous observations of the protoacoustic signal have employed linear accelerator, 6 synchrotron, [7][8][9][10][11][12][13][14][15][16][17] and tandem-accelerator 18 proton sources. Protoacoustic signals have also been observed using cyclotron-derived proton beams, 6,19 but these have used custom, modifiable beam lines originally built for research before they were applied to clinical therapy use, and the spill rise times were not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Hayakawa et al 8 have reported that the acoustic signal could also be measured at the surface of the patient's body when it is irradiated by the pulsed proton beam during treatment. This holds out the possibility of verifying the dose distribution during treatment, although several difficulties ͑such as the scattering and the absorption of the acoustic wave in vivo͒ would need to be overcome before this could become a reality.…”
Section: Iiib Calculation Of the Acoustic Waveformsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] It has been reported that the amplitude of the acoustic signal is proportional to the beam current from a macroscopic viewpoint. Sulak et al 1 investigated the dependence of the signal amplitude on the beam diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The recent proliferation of proton therapy centers has spurred a renewed interest in ionoacoustic range verification. Basic science experiments performed at national laboratories in the 1970s transitioned to clinically driven benchwork and clinical testing by the 1990s. Recently, measurements by individual receivers with lateral and distal offsets from the Bragg peak were simulated with an eye towards range verification.…”
Section: Introductionmentioning
confidence: 99%